From Waste to Worth: Integrating Circular Economy and Culinary Entrepreneurship for Sustainable Food Innovation in Emerging Markets - Aditiya Pratama Daryana; Prima Yudisthira; Vina Gabriella Saragih; Amalia Akita (Fakultas Kewirausahaan Universitas Garut, 2026)
This research aims to analyze the integration of circular economy and waste-based culinary entrepreneurship (Product of Waste / POW) in creating sustainable food innovations in emerging markets. The object of the study was 210 culinary business actors who adopted waste management practices. The method used is a mixed-method with a Structural Equation Modeling (SEM-PLS) approach to test the relationships between variables. The results of the study show that circular economy adoption and entrepreneurial capability have a significant effect on waste-based product innovation, with POW as the main mediator in improving sustainability performance. These findings confirm that the transformation of waste into economic value depends not only on the availability of resources, but also on entrepreneurial capabilities. This research contributes to the development of integrative models that support sustainable food innovation and increase the competitiveness of culinary businesses.